Penerapan Metode Scaffolding untuk Meningkatkan Kemampuan Operasi Aljabar Siswa SMP - Nurul Meilisa Putri; Susanti; Fitria (Jurnal Riset dan Pengabdian Masyarakat, 2022)
In learning mathematics, understanding concepts is very important for students because understanding is the most basic ability that students must have in the learning process. The low ability of students' understanding of mathematical problems because mathematics learning is still teacher-centered. The use of conventional learning models which resulted in low understanding abilities and learning outcomes. Therefore, teachers should be able to use learning models, one of which is learning by applying the Scaffolding method. The purpose of this study was to improve students' ability to operate algebra using the Scaffolding method. This research method is descriptive quantitative. The population of this study were students of class VII-1 and VII-2 of SMP Negeri 2 Banda Aceh. The research sample used was 6 students; 3 students in class VII-1 and 3 students in class VII-2. The data analysis technique used is descriptive statistics. While the data collection techniques in the form of observation and test data; pretest and posttest. The results showed that the score before the use of the Scaffolding method and after the use of the Scaffolding method respectively was 61.00 to 89.67 which means that the average score of students increased by 47%. Based on these values, it is concluded that the application of the Scaffolding method can improve students' algebraic operation skills.